Safe Administration of An Anti-PD-1 Antibody to Kidney-transplant Patients: 2 Clinical Cases and Review of the Literature. Issue 9 (November 2017) - Winkler, Julia K.; Gutzmer, Ralf; Bender, Carolin; Lang, Nina; Zeier, Martin; Enk, Alexander H.; Hassel, Jessica C.
Abstract : Antiprogrammed cell-death protein 1 (PD-1) antibodies have revolutionized therapy of metastatic melanoma and other tumors, but some subgroups of patients such as immunosuppressed patients after solid-organ transplantation, have regularly been excluded from clinical studies. We report 2 cases of kidney-transplant patients who received an anti-PD-1 antibody to treat metastatic melanoma. Treatment was tolerated well with no relevant adverse events and stable kidney functions, but the melanoma progressed in both patients. Factors potentially affecting risk of allograft rejection and response to treatment, for example, immunosuppressive regimen and therapeutic sequence, are discussed on the basis of current literature. Further studies are necessary to determine the risk of allograft rejection and the therapeutic benefit of anti-PD-1 antibodies for organ-transplanted patients, in particular as these checkpoint inhibitors have become therapeutic standard in a variety of tumors other than melanoma.